FAKTOR–FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2016) - Dianna Soegiharmanto Putri, 13.05.52.0054; Kartika, Andi (Students' Journal of Accounting and Banking, 2017)
The purpose of this research was to determine the effect size of the Public Accounting Firm (KAP), the size, growth of client companies, turnover manajamen, audit opinion, financial distress, to the auditor switching. This research uses explanatory study, the research describes the relationship between variables. The type or types of relationships in this study is a causal link between one or more variables. Samples were taken by using purposive sampling technique. Samples were 144 companies from 429 companies listed in Indonesia Stock Exchange in 2014-2016. Hypothesis in this research are tested by logistics regression analytical method in SPSS 23 sofware. The results indicate that firm size showed negative and significant effect on auditor switching. Size of client, growing of client company, Change of management, audit opinion and financial distress not showed effect on auditor switching.Keywords: Auditor Switching, Firm Size, Size of Client, Growth of Client Company, Change of Management, Audit Opinion and Financial Distress